Ecological Parameters of Outbreeding in the Interspecific Hybridization of the Common Carp - A. B. Khabzhokov; S. Ch. Kazanchev; O. O. Getokov; V. V. Fedyuk; L. A. Kazancheva; L. U. Yusupova; M. Kh. Liev (Юг России: экология, развитие, 2020)
Aim. To assess the quality of offspring obtained by the method of outbreeding combination (F1), Ukrainian scaly carp with the Romanian Fresinet breeding group for the biological intensification of the ecological parameters of fishponds.Material and Methods. Serving as materials for this work were new brood-stock of cultured breeds of carp. As an improver of the indicators carp of the Romanian Fresinet breeding group obtained in crossbreeding with Ukrainian breeds of carp of heterosis combinations (F1) were used. The studies were conducted during 2014-2017 in the ponds of the Sarsky experimental farm in the May district of the Kabardino-Balkaria Republic (V Ecological-Phenological Fish Breeding Zone).Results. The study of the growth of hybrid fry of F x Ukr. scaly, Ukr. scaly x F was undertaken during 2014-2017. The resulting data shows that F x Ukr. scaly, Ukr. scaly x F hybrids are significant competitors for purebred carp. When comparing the data obtained with the results of the joint rearing of test and control carp, it is clear that the economic effect of joint rearing is very significant in terms of economy of space and artificial feed.Conclusion. Heterosis in growth and viability manifested through the crossing of carp of groups of different breeds permits us to recommend the widespread use of industrial crossbreeding of F x Ukr. scaly (inbreeding) in carp farming and particularly in regions with a high temperature range, i.e. in the North Caucasus.